Assessment of climate change mitigation and changed cropping patterns for extensive periods at various scales (Plant Bulletin, 2025)
Climate changes arise due to drastic changes in weather patterns, temperature variations, drawdown water table, wind, and atmospheric pressure. To know farmers' perception about climate change and its impact on agriculture. A study was conducted in District Dir Lower (A hilly and rain-fed area with a subsistence farming system), Khyber Pakhtunkhwa, Pakistan. This study showed that there was a significant change in cropping patterns. The major crops still are wheat (90 % area), maize (Zea mays) and rice (Oryza sativa) (30 % and 29% area, respectively). At the same time, some of the crops were eliminated due to area limitations and economic benefits i.e. Opium (Papaver somniferum L.). The increase in the number of animals or their preferences and improved crop yield were not ascribed to climate change rather were correlated with improved production technologies and adaptation strategies. Study results showed that summer has prolonged (28 weeks) and winter is getting shorter (only 8 weeks) while spring and autumn have shrunk (about 4 and 3.5 weeks respectively) significantly or in some cases disappeared altogether. The monsoon rains are received about 4 to 5 weeks later while winter rains are received about 6 to 7 weeks later as compared to the past. The temperature of the four seasons (Winter, Spring, Summer and Autumn) has increased by 20, 27, 30 and 27% respectively. Water table depth was reported down (by about 30 to 40 feet) in various areas of the district, especially in the areas where eucalyptus trees were grown abundantly.
Keywords: Adaptations; Climate Change; Cropping Pattern; Seasonal Variations; Water Table